Weight loss and incidence of diabetes with the Veterans Health Administration MOVE! lifestyle change programme: an observational study. Issue 3 (March 2015) - Jackson, Sandra L; Long, Qi; Rhee, Mary K; Olson, Darin E; Tomolo, Anne M; Cunningham, Solveig A; Ramakrishnan, Usha; Narayan, K M Venkat; Phillips, Lawrence S
Summary: Background: Programmes for lifestyle change are aimed at improving health but little is known about their effectiveness in clinical settings. The Veterans Health Administration (VA) MOVE! lifestyle change programme is the largest in the USA. We investigated whether participation in MOVE! is associated with reduced incidence of diabetes. Methods: We did a retrospective observational analysis of data from VA databases in overweight patients and obese patients with a weight-related disorder who had undergone at least 3 years of continuous outpatient care in 2005–12. We used generalised estimating equations to assess characteristics associated with MOVE! participation, and Cox's proportional hazards regression to analyse the association between participation and diabetes incidence. Findings: Of 1·8 million eligible individuals, 238 540 (13%) participated in the MOVE! programme. 19 367 (1% overall, 8% of participants) met criteria for intense and sustained participation (at least eight sessions within 6 months over at least a 4-month span), which was associated with greater weight loss at 3 years than low-intensity or no participation (−2·2% vs −0·64% or 0·46%). Compared with non-participation, incidence of diabetes was reduced by intense and sustained participation (hazard ratio 0·67, 95% CI 0·61–0·74) and low-intensity participation (0·80, 0·77–0·83) in MOVE!. These patterns were consistent across sex, ethnic origin, and age. Participation was most beneficial in patients with high BMI or high random glucose concentrations at baseline (both pinteraction <0·0001). Interpretation: Participation in the MOVE! programme was associated with weight loss and reduced incidence of diabetes, but the rate of participation was low and, therefore, selection bias could have exaggerated these effects. Funding: US Department of Veterans Affairs, National Institutes of Health.